Who wants to be a millionaire? A game-based approach to enhancing engagement and teamwork in immunology education - Alessio Iannetti; Alessio Iannetti (Frontiers in Education)
Undergraduate Pharmacy students at Newcastle University reported difficulties with immunology topics, prompting the development of supportive seminar sessions. To determine the optimal teaching strategy, an experimental design was implemented over four academic years (2018–2022). In 2018–2020, half of the cohort participated in immunology seminars structured around open-ended group discussions, while the other half engaged in a competitive, team-based adaptation of Who Wants to Be a Millionaire?. The hypothesis was that the interactive, competitive nature of the game would enhance knowledge retention, student engagement and stimulation to teamwork. Students completed a pre-test (12 MCQs) before the main seminar activity and a post-test (six repeated and six new MCQs) to assess knowledge gain. A feedback form measured student perceptions of engagement and teamwork. In 2020–2022, due to the transition to online teaching, a mixed approach was adopted: all students participated in open-ended group discussions, but the MCQ pre-test and post-test assessments were gamified with a leaderboard. Results showed a statistically significant improvement in pre- to post-test scores across all formats, indicating that both game-based and traditional seminar approaches effectively supported knowledge retention. However, student feedback highlighted greater engagement and a stronger appreciation for teamwork in the game-based format. These findings suggest that game-based learning can enhance student motivation while maintaining learning outcomes achievements, supporting its integration into STEM curricula to promote active participation and teamwork skills.